Stylistic features of a letter from Imam Ali (peace be upon him) to Muawiyah (Czech Journal of Multidisciplinary Innovations, 2026)
The study reveals that the letters are characterized by protest, in addition to clarity of idea, avoidance of affectation and artificiality, their influence by Islamic meanings and the Holy Qur’an, simplicity of vocabulary, and strength of style in the era of early Islam. The analyzed text is built upon a core theme, namely paradox. All other stylistic features converge into this framework, organically interweaving the text so as to convey the meaning of the paradox that arises between the letter and its reply